New hemeroscopid (Odonata: Hemeroscopidae) from Lower Cretaceous Jinju Formation (South Korea) illustrating variation of wing vannal region among hemeroscopids and prohemeroscopids - Wei, Guangjin; Nam, Gi-Soo; Liu, Yuxuan; Ren, Dong; Wang, Yongjie (Zootaxa, 2026)
A new hemeroscopid species, Hemeroscopus jinjuensis Wei, Nam & Liu sp. nov., is described from the Lower Cretaceous Jinju Formation in the Jinju area of Gyeongsangnam Province, Republic of Korea based on the venational characteristics. The vannal region of wing is key for the taxonomy of Hemeroscopidae Pritykina, 1977, and compared to Prohemeroscopidae Bechly et al., 2002 the morphological variation of vannal region in Hemeroscopidae is outlined as follows: the anal loop enlarges and the MP–CuAa area expands, whereas the region between the basal and distal portions of CuAa, as well as the area between the anal loop and the anal triangle, becomes progressively reduced.